IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING REPORT TEXT THROUGH SEMANTIC MAPPING TECHNIQUE - Ivana Octaria (TRANSFORM : Journal of English Language Teaching and Learning, 2012)
This study deals with improving students’ achievement in writing report text through semantic mapping technique. This study was conducted by using classroom action research. The subject of the research was class VIII-2 SMP Swasta UPMI which consisted of 30 students. The research was conducted in two cycles; first cycle consist of four meetings and seond cycle consists of two meetings. The data have been collecting by using quantitative and qualitative data. The analysis showed that the improvement of students’ achievement in writing report text based on two cycles, namely the mean of cycle I is = 64,66, and the mean of cycle II is = 74, 3. It means that the implication teaching writing through semantic mapping technique can improve students’ achievement in writing report text. Key words : Semantic Mapping Technique, Writing, Report Text